(untitled) (JURNAL GEOCELEBES, 2025)
Earth’s geological structures are generally the result of tectonic processes. This study aims to determine the dimensions and direction of the geoelectric strike based on phase tensor analysis and 2D modeling to determine the subsurface structure in the Nullarbor area, South Australia using the magnetotelluric method. The magnetotelluric method is a passive geophysical technique used to create images of subsurface structures based on variations in rock resistivity. Data was obtained in EDI file mean the data has been processed and convert to apparent resistivity and frequency. Furthermore, data is analysis in the phase tensor process and then identify the Geoelectrical strike direction. Based on the tensor analysis, the results show that the study area has 2D dimensions, and the direction of the geoelectric cross section is from North to South, specifically N5°E. This geoelectric direction corresponds to the regional geological structure. After rotation in this direction, 2D inversion modeling of the MT data shows rock layers consisting of Eucla basins with sediment and volcanics rocks below 10 Ωm and Officer basin contain a sediment rock that has higher resistivity ranging from 10 to about 300 Ωm. Furthermore, the resistive layer with 300 – 2000 Ωm is expected as the upper crust in the central Coompana Province trending granite-rich corridor. This result show that the geological structure and lithology could be identified in this study area by analyzing the phase tensor and from the 2D model.